2012
DOI: 10.1128/aac.06428-11
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Analysis of a Prospective, Randomized, Double-Blind Trial Comparing Moxifloxacin and Clindamycin in the Treatment of Odontogenic Infiltrates and Abscesses

Abstract: The objective of this study was to identify the oral pathogens found in odontogenic infections, to determine their susceptibilities to amoxicillin-clavulanic acid (AMC), clindamycin (CLI), doxycycline (DOX), levofloxacin (LVX), moxifloxacin (MXF), and penicillin (PEN), and to search for associations between specific pathogens and types of infection. Swabs from patients enrolled in a randomized, double-blind phase II trial comparing MXF with CLI for the treatment of odontogenic abscesses or inflammatory infiltr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
30
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 17 publications
10
30
1
3
Order By: Relevance
“…In several studies, penicillins and cephalosporins do not attain satisfactory antimicrobial effect against some microorganisms and a shift of better effect towards the use of amoxicillin combined with clavulanic acid was noted (Kuriyama et al, 2005(Kuriyama et al, , 2007Warnke et al, 2008;Sato et al, 2009;Flynn, 2011). The additional use of clavulanic acid, which is irreversibly linked to the bectalamases, deactivating them and making the microorganisms sensitive to the penicillins, is therefore favoured by some authors (Kuriyama et al, 2005(Kuriyama et al, , 2007Rega et al, 2006;Sobottka et al, 2012). The results of more recent studies showed, that moxifloxacin was found to be more effective in the treatment of odontogenic abscesses (Cachovan et al, 2009(Cachovan et al, , 2011Sobottka et al, 2012), but is less cost effective compared with amoxicillin combined with clavulanic acid.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In several studies, penicillins and cephalosporins do not attain satisfactory antimicrobial effect against some microorganisms and a shift of better effect towards the use of amoxicillin combined with clavulanic acid was noted (Kuriyama et al, 2005(Kuriyama et al, , 2007Warnke et al, 2008;Sato et al, 2009;Flynn, 2011). The additional use of clavulanic acid, which is irreversibly linked to the bectalamases, deactivating them and making the microorganisms sensitive to the penicillins, is therefore favoured by some authors (Kuriyama et al, 2005(Kuriyama et al, , 2007Rega et al, 2006;Sobottka et al, 2012). The results of more recent studies showed, that moxifloxacin was found to be more effective in the treatment of odontogenic abscesses (Cachovan et al, 2009(Cachovan et al, , 2011Sobottka et al, 2012), but is less cost effective compared with amoxicillin combined with clavulanic acid.…”
Section: Discussionmentioning
confidence: 89%
“…The additional use of clavulanic acid, which is irreversibly linked to the bectalamases, deactivating them and making the microorganisms sensitive to the penicillins, is therefore favoured by some authors (Kuriyama et al, 2005(Kuriyama et al, , 2007Rega et al, 2006;Sobottka et al, 2012). The results of more recent studies showed, that moxifloxacin was found to be more effective in the treatment of odontogenic abscesses (Cachovan et al, 2009(Cachovan et al, , 2011Sobottka et al, 2012), but is less cost effective compared with amoxicillin combined with clavulanic acid.…”
Section: Discussionmentioning
confidence: 89%
“…31,36,39 New antibiotics such as moxiflacin in the treatment of dental infections offer another alternative that showed a high in vitro activity against odontogenic bacteria associated with dental abscesses and infiltrates in randomized clinical trials. 40 Dental infection is a polymicrobial mixture organized as a biofilm, its composition depends on several factors such as bacterial identification methods (traditional microbiology, PCR, real time-PCR, checkerboard DNA-DNA hybridization and pulse-field gel electrophoresis), sample size, asymptomatic or symptomatic infections, presence or absence of pulp necrosis, sampling method, region of the root canal, and sociodemographic traits. 1,3,7 There is little information about the bacteria taxa involved in the primary and mixed dentitions, but there is general agreement that dental infections are polymicrobial with a predominance of anaerobic Gram-negative species, especially in the final stages of the infections as clinical symptoms become apparent.…”
Section: Discussionmentioning
confidence: 99%
“…Jų atsiradimas priklauso nuo anatominių ir imuninių organizmo savybių bei patogeno virulentiškumo [6,7]. Dažniausiai tai polimikrobinė infekcija, sukelta Viridans grupės streptokokų, auksinio stafilokoko ir/ar anaerobinių, gramneigiamų mikroorganizmų [7][8][9][10]. Infekcijų vystymuisi sudaromos tinkamos sąlygos esant užleistoms ar netinkamai gydomoms burnos ligoms.…”
Section: įVadasunclassified
“…Nesuteikus reikiamos pagalbos, patogenas gali išplisti į bet kurį organą, sukeldamas gyvybei pavojingas būkles: sepsį, sepsinį šoką, mediastinitą, meningitą, kaverninio sinuso trombozę, smegenų abscesą ir kitas patologijas. Įvairių autorių duomenimis, ypač pabrė- [7,8,[13][14][15][16].…”
Section: įVadasunclassified